Swelling of Nuclear Fuel in Nuclear Reactors - Mirteimour, M. (New Trends in Physical Science Research Vol. 3, 2022)
An attempt was made by inelastic scattering of nucleons on nuclei to elucidate the reasons for the excitation of nuclei in nuclear chain reactions, as well as the deformation of nuclei and the swelling of atoms. The proposed distorted-wave theory of multiple scattering of nucleons by nuclei is applied. When studying the properties of excited nuclei, the connections of the quadrupole vibrations of the nuclear surface with the motion of nucleons by the corresponding dipole and quadrupole giant resonances were taken into account. The energies spent on the excitation of giant dipole and quadrupole resonances with the corresponding energies and excitation widths, as well as on the vibrations of the nuclear surface, are determined. For a certain time, being in an excited state, the nucleus deforms and increases its size and the size of the atom, that is, its swelling.